Upaya Menumbuhkan Karakter Anak dalam Pembelajaran Sastra Anak dengan Model Play-Learning dan Performance-Art Learning di SDN Banyuajuh 4 - Wahid Khoirul Ikhwan (Program Studi Pendidikan Guru Sekolah Dasar)
One innovation of learning to improve writing skills is to use direct and Play-Learning dan Performance-Art Learning. By applying this approach more classes are expected to live and be happy to follow the students' learning Indonesian from the results of performance tests Cycle I and Cycle II of the above can be concluded that: there is an increase from Cycle I to Cycle II. On Cycle II all students understand the material completely written narrative of the interview, through changing direct sentence (original interview) into indirect sentences (narratives). So it can be concluded that the cooperative learning model is more successful / better than the direct learning model.